Implications of Item Keying and Item Valence for the Investigation of Construct Dimensionality - Seng Kam, C.; Meyer, John (2015)
Factor analysis and nomological network analysis are commonly used as complementary procedures in the investigation of the dimensionality of constructs (e.g., self-esteem, job satisfaction). Although it has been demonstrated that factor analyses are often biased toward a two-dimensional solution for measures including regular- and reverse-keyed items, less attention has been paid to the implications for nomological network analyses. We propose, and demonstrate empirically in two studies, that item keying is confounded with item valence (i.e., favorability of item content), and that item valence can bias the results of both factor analysis and nomological network analysis toward a two-dimensional interpretation. We also demonstrate that the valence effect is related to, but distinguishable from, social desirability response bias. We caution that the practice of excluding reverse-keyed items to achieve unidimensionality can lead to distortion in correlations among constructs, and we offer alternative remedies to the valence problem.